Development of FUNCHEM Educational Game Based on Integrated Chemo edutainment Ability Critical Thinking Skills of High School Students on Colloid Material - Azmi, Al; Zurweni, Zurweni; Miharti, Isra (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
The research aims to develop the funchem educational game based on a chemo-edutainment approach integrated with critical thinking skills as an instructional medium for the topic of colloids. The research was driven by the low level of students critical understanding of colloidal concepts and the prevalent use of conventional teaching methods that tend to be monotonous. The chemo-edutainment approach, which merges educational content with entertaining elements, is considered to have the potential to create a more engaging and enjoyable learning experience. The research employed a Research and Development (RD) design, adopting the Lee and Owens model, which encompasses five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The findings of this study indicate that: (1) the development process of the educational game involved a series of steps including needs analysis, media design, product development, and classroom implementation; (2) expert validation results from both content and media reviewers categorized the game as